Isolation and characterization of bacterial strains that are resistant to zinc and iron in different soil environments - Intan Nurliyana, Omar (Universiti Malaysia Sarawak, (UNIMAS), 2011)
A total of 32 heavy metal resistant bacterial strains were obtained from Molecular Genetic Microbial Culture collection. Nineteen of the bacterial strains were found to be resistant against Zn and Fe with different patterns of resistance. The resistance pattern ZnSFeR shows the highest frequency. The levels of resistance of all 19 strains were tested using minimal inhibitory concentration (MIC). From the result obtained, it was observed that zinc was more toxic as it can totally inhibit bacterial growth at 500µg/ml as compared to iron which still had bacterial growth at the same concentration. Six selected bacterial strains which acted as representative for each patterns of resistance were used for subsequent tests including UV resistance, catalase activities and citrate production. The test done showed that some of them were able to tolerate to UV radiation and react positively in catalase test thus indicating that they were aerobic bacterial strains.